Analisis antropometri tubuh dan tingkat kebugaran jasmani pada peserta kegiatan ekstrakurikuler futsal di SMK Negeri 13 Malang - Prayoga, Arda Septian; Nurrochmah, Siti (Jurnal Porkes, 2024)
Futsal extracurricular activities seem to experience significant fatigue and are unable to show optimal results, researchers feel that futsal extracurricular activity participants do not have ideal body anthropometric posture. This study aims to determine and assess the anthropometric condition of the body and the level of physical fitness. This method uses a descriptive survey design with an observation approach. Data were analyzed with quantitative descriptive statistics. The population was 40 students and the sample used total sampling. Instruments using tests and non-tests. Anthropometric test instruments in the form of height tests, weight tests, arm length tests, and leg length tests. Indonesian physical fitness test instrument (TKJI). Non-test in the form of observation, namely observing the testi. The data was then analyzed with the help of SPSS software using quantitative descriptive statistics in the form of central tendency. The anthropometric results of the height test dominant participants in the criteria are very less (67.5%), the weight test participants in the criteria are very less (60%), the arm length test dominant participants in the criteria are less (45%), the leg length test dominant participants in the long criteria (45%). It can be concluded that the level of physical fitness in futsal extracurricular students is mostly in the less category (82.5%).